The Use of Teaching and Learning Strategies from Alterity in the Commercial Education Major at Universidad Nacional - Agüero Flores, Alejandra (2024)
From otherness, the use of teaching and learning strategies is proposed as a resource in the classroom that allows the inclusion and equality of students in the teaching and learning processes in the Commercial Education career; The teacher, being aware of the needs and interests of the students, will be able to use strategies that promote the development of skills and strengths so that everyone has the same opportunities. Likewise, graduates will be able to use strategies that romote otherness, creating spaces for horizontal and emancipatory communication in their work areas. In order to identify how teachers in this career can apply otherness in teaching and learning strategies, it is important to ask the following question: will the teacher be discovering the needs of the students? .In order to respond to this statement, the concept of alterity that is the discovery of the other, that is, that there are different contexts and worldviews, will be addressed. In which, it is required that the teacher is located in the educational realities that his students present and that they look for a solution so that the activities carried out respond to their needs